Critical Care Nurses’ Knowledge, Attitudes, and Perceived Barriers towards Pressure Injuries Prevention - Batiha, Abdul-Monim (International Journal of Advanced Nursing Studies, 2018)
Background: Pressure injuries are a considerable problem for hospitalized critically ill and elderly patients, as such injuries produce pain, and reduce total wellbeing, resulting in increased morbidity and mortality, as well as often extending those patients’ hospital staysPurpose: The purpose of this study was to determine critical care nurses knowledge, attitudes, and perceived barriers toward pressure injuries prevention.Design: A descriptive cross-sectional survey was performed, using a questionnaire method to critical care nurses’. The study took place between August and October 2017 and involved ten hospitals: two university hospital, six public hospitals, and two private hospitals.  Methods: Data were collected by means of a questionnaire using two valid and reliable instruments: i) the Pressure Ulcer Knowledge Assessment Tool 2⋅0, and ii) Attitude Toward Pressure Ulcer Prevention and two newly developed instruments sociodemographic and perceived barriers toward pressure injury prevention.Results: The entire mean knowledge score for the participants was 54.9%, and overall high attitude scores were 76.7%. Level of education, years employed in a critical care unit, training received on pressure injury prevention, and the number of papers read on pressure injury prevention was all identified as having a significant and independent effect on participants’ knowledge concerning prevention of pressure injuries. To evaluate the effect of demographic characteristics on nurses’ attitudes, the only significant variable was "years of employment in critical care units". Shortage of staff was the most commonly cited barrier faced by critical care nurses’ during practice.
Keywords: Attitudes; Barriers; Critical care nurses’; Jordan; Knowledge; Pressure injuries